Binding of phosphorothioate oligodeoxynucleotides to basic fibroblast growth factor, recombinant soluble CD4, laminin and fibronectin is P-chirality independent. - Benimetskaya, L (1995)
Antisense oligodeoxynucleotides can selectively inhibit the expression of individual genes and thus have potential applications in anticancer and antiviral therapy. A critical prerequisite to their use as therapeutic agents is the understanding of their non-specific interactions with biological structures, e.g. proteins. In this study we examined the interactions of P-chiral phosphorothioate oligodeoxynucleotides with several proteins. The Rp- and Sp- diastereomers, and racemic machine-made mixtures, or M-oligodeoxynucleotides were used independently as competitors of the binding of a probe, phosphodiester oligodeoxynucleotide bearing a 5' alkylating moiety, to rsCD4, bFGF and laminin. These oligodeoxynucleotides were also used as competitors of the binding of a non-alkylating probe M-phosphorothioate oligodeoxynucleotide, 5'-32P-SdT18 to fibronectin. The average values of and quantitative estimates for the IC50 of competition and the constant of competition (Kc) of Rp-, Sp- and M-stereoisomers of several homo- and heteropolymer oligodeoxynucleotides were determined and compared. Surprisingly, in the proteins we studied, the values of IC50 and Kc for the Rp-, Sp- and M-oligodeoxynucleotides were essentially identical. Thus, the ability of the phosphorothioate oligodeoxynucleotides we employed, to bind to the proteins studied in this work, is virtually independent of P-chirality. Our results also imply that the role of the purine and pyrimidine bases in oligodeoxynucleotide-protein interactions, as well as the nature of the contact points (sulfur versus oxygen) between the oligomer and the protein, may be relatively unimportant.